2018
DOI: 10.9734/sajrm/2018/v2i129234
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Property of Ethanolic Leaf Extract of Eucalyptus citriodora Hook on Clinical and Typed Isolates of Escherichia coli

Abstract: The emergence of antibiotic resistance bacteria, necessitated the discovery and development of alternative therapy to bacterial infections. This work assessed the inhibitory property of ethanolic leaf extract of Eucalyptus citriodora against clinical isolate and E. coli ATCC 35218. Agar well diffusion test was used to determine the antibacterial activity of the extract on both isolates of E. coli. For both isolates, no zone of inhibition was observed at concentrations of the extract between 50-150 mg/ml, but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…According to Missanjo and Mkwezalamba (2016), the essential oil of C. citriodora inhibits the growth of the human pathogens Escherichia coli and Staphylococcus aureus. Similarly, Muhammed, Dada, Alo (2018) report that ethanol extracts of lemon-scented gum at 200-500 mg/ml also inhibited the human pathogen E. coli. Later, Insuan and Chahomchuen (2020) also observed antibacterial activity of its essential oil against Bacillus subtilis, S. aureus, S. intermedius, E. coli and Pseudomonas aeruginosa.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…According to Missanjo and Mkwezalamba (2016), the essential oil of C. citriodora inhibits the growth of the human pathogens Escherichia coli and Staphylococcus aureus. Similarly, Muhammed, Dada, Alo (2018) report that ethanol extracts of lemon-scented gum at 200-500 mg/ml also inhibited the human pathogen E. coli. Later, Insuan and Chahomchuen (2020) also observed antibacterial activity of its essential oil against Bacillus subtilis, S. aureus, S. intermedius, E. coli and Pseudomonas aeruginosa.…”
Section: Discussionmentioning
confidence: 85%
“…Likewise, C. citriodora is reported to have antimicrobial properties (ESTANISLAU; BARROS; PEÑA, 2001, MAHMOUD;EBRAHIM;ALY, 2004, MISSANJO;MKWEZALAMBA, 2016, MUHAMMED;DADA;ALO, 2018, MIGUEL et al, 2018CHAHOMCHUEN, 2020), insecticide (NEGRINI et al, 2018) and anthelmintic (ARAÚJO-FILHO et al, 2019). According to Mulyaningsih et al (2011), some active and bactericidal compounds present in lemonscented gum essential oil are aromadendreno, 1,8-cineol, citronellal and citronellol, which explains the potential for inhibiting Xanthomonas spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five hundred grams (500g) of the pulverized leaf powder was macerated in 4,500ml of 75% ethanol and 75% methanol for 72 hours and then filtered using Millipore (pore size 0.7µm) filter paper respectively. Using rotary evaporator set at 40 o C, the filtrates were concentrated to recover the ethanolic and methanolic extracts [15]. The weights of the dried extracts were measured and the percentage (%) yields were calculated as follows:…”
Section: Preparation Of Leaves and Extractsmentioning
confidence: 99%
“…Some studies of essential oil and extracts from eucalyptus have reported acaricidal activity (SOUZA et al, 2016), bioactivity against Zabrotes subfasciatus (SAMPAIO et al, 2017), in addition to good antimicrobial and antioxidant properties (CARDOSO et al, 2019;MUHAMMED et al, 2018;SYUKRI et al, 2019). However, most research is related to essential oil, or the use of the wood for extraction instead of leaves.…”
Section: Introductionmentioning
confidence: 99%